MEDIA IMPACT ON STUDENTS: MEDIA LITERACY LEVELS AND SMARTPHONE INTEGRATION IN HIGHER EDUCATION - Khan, Sharoz Ahmad; Pandey, Sumit Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today's digital age, students are constantly exposed to a multitude of media messages daily. To effectively comprehend and engage with these media texts, students must possess media literacy skills, which should be integrated into the school curriculum. Smartphones, one of the primary sources of media exposure for students, play a significant role in their lives. Given teachers' crucial impact on students, incorporating media literacy skills into teaching pedagogy could be instrumental in integrating media literacy and mobile education into the classrooms. This study employed a cross-sectional and descriptive research design to gather data from 100 students and 30 teachers through mixed questionnaires and focus group discussions. This research delves into the critical topic of media literacy and its influence on students. It explores the relationship between students and teachers and how this dynamic can be leveraged to enhance the learning experience. Ultimately, this paper serves as a call to action for school administrators to thoughtfully design guidelines for incorporating smartphones into their curricula. The overarching goal is to inspire productive discussions and strategies for utilizing media tools to engage students and inculcate classroom media literacy.